Psychological Aspects of a Police Officer’s Professional Success - M. V. Butenko (Bulletin of Kharkiv National University of Internal Affairs)
The article analyses the general concept of human success from various psychological and scientific perspectives, as well as the concept of “a police officer’s professional success” separately, since it plays an important role for both the individual and society at the present stage of society development. The author emphasises that at the scientific and legislative levels there are no explanations and clarifications as to who is a professionally successful police officer. The study provides a generalised analysis of police officers’ powers, among which the main ones are highlighted which every police officer must perform regardless of their position, length of service and other factors. The importance of professional training of police officers during their service is also emphasised.